2021
DOI: 10.1186/s40537-021-00524-9
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning-based identification of patients with a cardiovascular defect

Abstract: Cardiovascular diseases had been for a long time one of the essential medical problems. As indicated by the World Health Association, heart ailments are at the highest point of ten leading reasons for death. Correct and early identification is a vital step in rehabilitation and treatment. To diagnose heart defects, it would be necessary to implement a system able to predict the existence of heart diseases. In the current article, our main motivation is to develop an effective intelligent medical system based o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 28 publications
0
14
0
Order By: Relevance
“…Notably, studies have found that utilizing a subset of features yields better performance compared to using all available features [10]. The ROC curve visually illustrates the trade-off to between the true positive rate and the false positive rate for a binary classification model across different classification thresholds, aiding in model evaluation and comparison [11]. The test outcomes reveal a True Positive Rate (TP Rate) of 0.943 in the PCR Area, along with an ROC Area of 0.976 Class.…”
Section: IIImentioning
confidence: 99%
“…Notably, studies have found that utilizing a subset of features yields better performance compared to using all available features [10]. The ROC curve visually illustrates the trade-off to between the true positive rate and the false positive rate for a binary classification model across different classification thresholds, aiding in model evaluation and comparison [11]. The test outcomes reveal a True Positive Rate (TP Rate) of 0.943 in the PCR Area, along with an ROC Area of 0.976 Class.…”
Section: IIImentioning
confidence: 99%
“…There have already been several research on the topic of predicting nutritional status and finding their factors using the machine learning (ML) approach. Multiple illnesses have been predicted using ML systems such as anemia [ 28 , 29 ], acute appendicitis [ 30 ], cardiovascular defect [ 31 ], covid 19 [ 32 , 33 ], diabetes [ 27 , 34 37 ], hypertension [ 38 ], low birth weight [ 39 42 ] utilizing a variety of demographic and health survey datasets as well as common risk factors of the diseases. Several studies had been conducted previously based on malnutrition using machine learning approaches.…”
Section: Introductionmentioning
confidence: 99%
“…Some healthcare applications and services are digitally accessible via a mobile device. Self-monitoring has the potential to improve health daily [15]. The purpose of this evaluation is to establish the present demand and market offer, as well as to identify chances for excellent health.…”
Section: Introductionmentioning
confidence: 99%